2018
DOI: 10.1002/slct.201801117
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Inspired Topology Directed Synthesis of Hybrid Macrocyclic Compounds: A Simple Approach to Natural Product Analogues

Abstract: Herein we report a new approach of designing natural product‐like macrolide analogues by combining the critical structural features of two different class of natural products. These critical structural features are structural motifs that are commonly present in each class of selected family of natural products. These molecules are synthesized by using Steglich esterification and ring‐closing metathesis as key reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 92 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…14,[19][20][21] The acquiring of more NPs is in line with what several studies have reported about the advantages of NPs over combinatorially synthesized compounds in the search of biologically relevant and privileged scaffolds. [22][23][24][25][26][27][28][29][30][31][32][33] Principal component analysis (PCA) between NPs, marketed drugs, and synthetic compounds conrmed the aforementioned statement by revealing that combinatorial compounds covered a well-dened and restricted area while drugs and NPs occupied approximately the same chemical space-covering almost all of the combinatorial compounds' diversity space as well as a much larger additional volume. 17,20,21,[30][31][32][33][34][35][36][37][38][39] Designing such NP analogues being inspired by nature is almost impossible, thus, it is necessary to emphasize that the place of NPs remains unique.…”
Section: Fidele Ntie-kangmentioning
confidence: 99%
See 2 more Smart Citations
“…14,[19][20][21] The acquiring of more NPs is in line with what several studies have reported about the advantages of NPs over combinatorially synthesized compounds in the search of biologically relevant and privileged scaffolds. [22][23][24][25][26][27][28][29][30][31][32][33] Principal component analysis (PCA) between NPs, marketed drugs, and synthetic compounds conrmed the aforementioned statement by revealing that combinatorial compounds covered a well-dened and restricted area while drugs and NPs occupied approximately the same chemical space-covering almost all of the combinatorial compounds' diversity space as well as a much larger additional volume. 17,20,21,[30][31][32][33][34][35][36][37][38][39] Designing such NP analogues being inspired by nature is almost impossible, thus, it is necessary to emphasize that the place of NPs remains unique.…”
Section: Fidele Ntie-kangmentioning
confidence: 99%
“…and (iii) How should such a biological/diversity-oriented synthesis be planned? 17,[22][23][24][40][41][42] NP databases and in silico-based methods Low hit rates aer screening large synthetic combinatorial databases le drug discoverers the choice to either increase the diversity of combinatorial databases through improved diversity of synthetic reaction(s) and/or make a return to NPs which have worked in the past. 43 Historically, NPs have played a signicant role in drug discovery, particularly for cancer and infectious diseases.…”
Section: Fidele Ntie-kangmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrocyclic scaffolds are omnipresent in naturally occurring compounds [ 70 ] whose synthesis can be achieved by employing ring-closing metathesis and Steglich esterification [ 71 , 72 ]. Thiacladospolide is a sulfur containing natural product obtained from marine sources.…”
Section: Literature Reviewmentioning
confidence: 99%